ICT-Based Lombok Disaster Management Communication Model in Indonesian (Sociología y tecnociencia, 2023)
When a natural disaster occurs, information and communication technology (ICT)-based disaster communication must be carried out, especially from the government to the affected community. The needs for information on the location and the number of victims and data collection on their needs are highly required to ease officers and volunteers to assist disaster victims. When an earthquake occurred on July 29, 2018, the community was in a state of panic, anxiety, and fear, making it prone to the confusion of information, resulting in slow disaster management. This study aims to determine the communication model of Lombok earthquake disaster management based on ICT carried out by the Public Relations of the North Lombok Regency Government to the people of Gangga Village, North Lombok. This research utilized a descriptive qualitative method by conducting in-depth interviews with the Public Relations of the North Lombok Regency Government, the people of Gangga Village, North Lombok Regency, and the North Lombok Regional Disaster Management Agency (BPBD). The results disclosed that the ICT-based disaster communication model during the July 29, 2018 earthquake integrated related Regional Work Units (SKPDs), such as the Public Relations, BPBD, Public Works Service, and Health Service through Handy Talky (HT), Hand Phone (HP), websites, and social media. The North Lombok Regency Government also explicitly coordinated with the Ministry of Communication and Information, who asked the NTB Regional Frequency Spectrum Monitoring Center to continuously coordinate with telecommunications operators, ORARI, and RAPI in NTB to ensure excellent telecommunications services for the community
Keywords: Disaster Communication; Information and Communication Technology (ICT); Model